Evaluation of heating rate on the pyrolysis of residual biomass for biochar production - Batista, Gabriel de Freitas (2022)
Biochar is a carbon-rich solid product of biomass thermal conversion, which contains several properties for a wide range of applications that promote the attention of industries and researchers. The porous structure of char particles enables its application as soil fertilizer, adsorbent, catalyst, among others [1]. In this context, biomass is a critical resource, as it can be used for biochar production at the same time produce renewable energy, being able to mitigate climate change phenomena. There are many advantages to using biomass as an energy source, namely its carbon neutrality and being a nonpolluting source. In this context, the main technologies for fuel and/or energy production from biomass are pyrolysis, gasification, or combustion [2]. Among technologies for biomass conversion, pyrolysis is widely used, consisting of a thermal decomposition process in absence of oxygen, to convert biomass into biochar, bio-oil and gases, generating no waste during the process